Risk management in the airline industry / Shahrul Anuar Daud and Maszuwita Abdul Wahab - Daud, Shahrul Anuar; Abdul Wahab, Maszuwita (2021)
Airline is one of property that very much exposed to risk. The airlines industry has to take seriously on the customer side to give better services and management. Malaysia Airlines (MAS) recorded the highest complaint followed AirAsia and Malinda Air.Risk management is a crucial part in managing activity and a major factor to define the success of a project by handling any risk. Therefore, Airlines is very much focused lately during the pandemic of Covid-19. The aim of this study is to provide an overview on the risk management in airlines industry in Malaysia in terms of technology and people that experienced by the consumer of the airline. Therefore, the awareness of risk management is important to create the effectiveness and efficiencies of the organizations.